Interpreting textual artefacts: cognitive insights into expert practices - Tarte, S (Digital Humanities Institute, 2012)
Ancient textual artefacts are the substrate of our scholarly knowledge of ancient civilisations. This knowledge is discovered, extracted, and created through the daily practice of interpretation of these ancient documents. The cognitive aspects of this act of knowledge creation are at the core of the research presented in this paper. In order to identify the various cognitive processes that are mobilised to extract meaning from ancient and difficult to read textual artefacts, I have observed how papyrologists approach the task of interpreting Roman stylus tablets and how assyriologists study tablets written in an as-yet-undeciphered script, Proto-Elamite. Linking these observations with findings from the cognitive sciences, I have identified perceptual processes that establish a visual feedback loop, a kinaesthetic feedback loop, and an aural feedback loop. These feedback loops only become effective sense-making mechanisms if they integrate processes that allow for knowledge to grow. These processes are conceptual processes that involve semantic memory, structural knowledge as well as insight, creativity and collaboration.